Detecting Inconsistent Responding on the Youth Psychopathic Traits Inventory–Short Form. (April 2019) - Kelley, Shannon E.; Edens, John F.; Donnellan, M. Brent; Somma, Antonella; Fossati, Andrea; de Ruiter, Corine; Eisenbarth, Hedwig; Vaughn, Michael G.
The Youth Psychopathic Traits Inventory–Short Form (YPI-S) is a convenient measure for assessing psychopathy in settings with constraints on resources. However, the YPI-S does not contain a means of detecting careless or random response styles. The present study describes the development and evaluation of an inconsistent responding scale for the YPI-S using five archival samples that vary in language (English, German, Italian, Dutch) and other participant characteristics (juvenile offenders, adolescent students). Inconsistency scores resulting from the new scale effectively distinguished genuine participant responses from randomly generated cases (area under the ROC curve [AUC] = .85-.90) and from cases in which 50% of original responses were replaced with random data (AUC = .75-.82). The associations between the YPI-S and theoretically relevant correlates were reduced among participants exceeding proposed cutoff scores for profile validity compared with associations among more consistent respondents.